Conflict Management between State 6 Tondano Junior High School Students in the Industrial Era 4.0 - Sumolang, Nortje (JR Education, 2025)
Personality covers all ages, both physical and psychic, so it can be known that every action and behavior of a person is a reflection of a person's personality. Many conflicts occur in educational organizations and the future is likely to increase. The purpose of this research is to find out the causes of conflicts between students through more in-depth research. The method used is a qualitative method with data collection carried out by interviewing 19 students. The results of this study show that various conflicts occur among students such as mocking parents, mocking friends, misunderstandings, disrupting, rude, and stealing writing stationery. This study recommends strategies, namely using a problem-solving approach and a character development approach for the younger generation.